Rebranding Samosir Island As City of Foreign Tourists (Jurnal Bina Praja, 2023)
Tourism contributes greatly to a developing country as one of the driving sectors of the economy. The government and the management of tourist destinations must consistently improve the quality of tourism in terms of destinations, industries, institutions, and marketing because of the scope of tourism and the movement of millions of people on indirect tourist trips. So far, foreign tourists have become familiar with tourist destinations in Bali and Lombok. However, many tourist destinations in Indonesia have not been maximally introduced, like Samosir Island at Lake Toba Region. In 2016, the Government of Indonesia envisioned making Toba become the Monaco of Asia. This article examines the factors affecting how long visitors from other countries remain when vacationing in Samosir, a popular international travel destination in Indonesia. Using 100 hundred samples of international travelers' empirical modeling is carried out using a quantitative approach through Ordinary Least Squares (OLS) and descriptive analysis. The quality of the accommodations, infrastructure, and rising travel costs contribute to longer travel time for tourists. Although it does not considerably shorten the length of stay in Samosir, rising vacation expenditures in other locations are a bonus for adventurous foreign tourists in Indonesia. Although the appeal of nature and its peace appeal to visitors from abroad, income levels do not greatly raise demand for international visitors to Samosir. As an effort, brand management is needed to improve the image of Samosir Island as the city of foreign tourists in Indonesia.
Keywords: foreign tourist; international tourism; city branding; Samosir